Multiple factors correlating with wing malformations in the population of Parnassius apollo (Lepidoptera: Papilionidae) restituted from a low number of individuals: A mini review. (26th December 2017) - Pierzynowska, Karolina; Skowron Volponi, Marta; Węgrzyn, Grzegorz
Abstract: The Apollo butterfly, Parnassius apollo (Linnaeus), was common in Europe over 100 years ago, but currently it is considered as near threatened. Different conservation programs have promoted the persistence of this species; however, it is still endangered. An example of such programs was the action devoted to reestablish the Apollo butterfly population in Pieniny National Park (Poland) from only 20–30 individuals which had survived till the last decade of the 20th century. This reintroduction has been successful; however, unexpected developmental problems appeared. Butterflies with deformed or reduced wings became frequent in the population living in the natural habitat, and particularly among those reared under seminatural conditions (in the same environment, but fenced by a net). Until recently, reasons for these malformations remained unknown. However, reports published during last months indicated that there are genetic, biochemical, and microbiological factors contributing to this phenomenon. In the malformed individuals, lesions in the wingless gene and dysfunctions of laccase 1 and 2 were found to be significantly more frequent than in normal insects. A large fraction of butterflies with deformed or reduced wings was devoid of the prokaryotic symbiont Wolbachia, which was present in most normal individuals. Moreover, Yersinia pseudotuberculosis (Pfeiffer) Smith and Thal, and Serratia sp., bacteria pathogenic to insects, were detected in the biological material from both normal and malformed butterflies from this population. These findings are summarized and discussed in this review, in the light of conservation of insects and restitution of their populations from a low number of individuals.